Prognostic role of immunohistochemical analysis of 5 mc in myelodysplastic syndromes. (28th June 2013) - Poloni, Antonella; Goteri, Gaia; Zizzi, Antonio; Serrani, Federica; Trappolini, Silvia; Costantini, Benedetta; Mariani, Marianna; Olivieri, Attilio; Catarini, Massimo; Centurioni, Riccardo; Alesiani, Francesco; Giantomassi, Federica; et al.
Abstract Background Aberrant DNA methylation at CpG islands within promoters is increasingly recognised as a common event in human cancers and has been associated with the silencing of important tumour suppressor genes. Epigenetic therapy using hypomethylating agents has demonstrated clinical effectiveness; the drugs azacitidine and decitabine have been approved for the treatment of MDS. Method We investigated the association between global DNA methylation and clinical outcome in MDS. We evaluated 134 MDS bone marrow trephine biopsies (BMTB) by immunohistochemistry and compared the results with those from an age‐matched group of normal BMTB. Immunohistochemistry was performed on paraffin‐embedded sections using the anti‐5‐methylcytosine (5mc) antibody. Results Our results showed that the 5mc immunostaining score (M‐score) of patients with MDS was higher than those of normal controls and that overall survival significantly correlated with global DNA methylation, age and IPSS score. Therefore, we found that patients with high levels of methylation had a shorter median overall survival (OS) compared with patients with lower levels. These immunohistochemistry results were confirmed by analysing global DNA methylation on LINE‐1 sequences using the COBRA method and pyrosequencing. Conclusion This study reports that global DNA methylation detected by immunohistochemistry predicts OS in MDS.